Understanding oncological and sexual function outcomes with gynaecological organ preserving cystectomy in women with bladder cancer; a systematic review - Rebecca Martin; Harriet Wylie; Charlotte Moss; Shaista Hafeez; Pardeep Kumar; Anne Marie Rafferty; Mieke Van Hemelrijck (BJUI Compass)
Abstract Introduction and Objectives Cystectomy for bladder cancer (BC) in women involves removing gynaecological organs and the anterior vaginal wall, significantly impacting sexual function (SF). Gynaecological organ‐preserving cystectomy (GOPC) aims to minimise toxicity, but limited studies assess its impact. We reviewed existing evidence. Methods A systematic review was conducted using Ovid (Medline, Embase, PsycINFO, CINAHL) and Cochrane Library. Studies assessing survival and SF outcomes of GOPC and SF outcomes of standard cystectomy were included. Results Fourteen studies (1049 screened) reported on small cohorts (11–41 patients). Most GOPC patients had ≤T2b N0 M0 disease, while standard cystectomy patients had up to T4/N1. In the GOPC cohort median follow‐up was 36 months. Over a 16–70 month period, Disease‐Free Survival in GOPC patients was 80–100%. Due to heterogeneity in Patient‐Reported Outcome Measures (PROMS), a narrative analysis was performed. GOPC patients reported high levels of sexual activity, reduced dyspareunia and moderate‐to‐high satisfaction. While SF initially declined, recovery improved over time, with Female Sexual Function Index (FSFI) scores exceeding the 26.2 dysfunction threshold in two studies by 12 months. In standard cystectomy, sexual dysfunction was common, with varying distress levels and inadequate patient counselling. Conclusions Understanding the outcomes of GOPC is limited by study design and measurement variability, and meta‐analysis was not possible. In this narrative review, oncological outcomes in the GOPC group appears to have equivalent oncological outcomes to a standard radical cystectomy in carefully selected female patients. Sexual recovery outcomes in either complete or partial sexual organ preserving cystectomy appear to be better than a standard female radical cystectomy. Further prospective studies, particularly those involving nerve‐sparing surgery, are needed. Women undergoing either standard cystectomy and GOPC commonly experience sexual dysfunction, and there is a need to improve pre‐ and post‐operative counselling.